Evaluating atmospheric pressure cold plasma decontamination techniques for packaging materials: a systematic review and meta-analysis - Maccaferri, Caterina; Gherardi, Matteo; Laurita, Romolo (Frontiers in Physics, 2024)
Decontaminating food packaging surfaces is a crucial step in the food processing industry to ensure the quality and safety of the product. Decontamination is intended as a procedure aimed to reduce the microbial load present on contaminated packaging to a safe level. Several techniques are traditionally employed, but the industry is seeking innovative methods that could offer economic and environmental benefits. Cold plasma is emerging as a promising solution among the range of possibilities. The present review aims to assess the effectiveness of plasma-assisted systems for decontaminating packaging materials. A systematic collection of inherent records was carried out, and the study outcomes were extracted using the protocol for meta-analysis. The synthesis of the results demonstrates the efficacy of this sanitation technique, since the average logarithmic reduction of the pathogen charge on the packaging was above 4. This outcome is promising since it aligns with standard requirements for traditionally employed antiseptics. Future research should focus on the optimization of processes from the perspective of industrial applications.